Exploring The Barriers That Hinder the Effective Use of Technologies in EFL Classrooms During COVID-19 - Khoso, Parus Abdul Qadir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This study investigates the barriers that hinder the effective use of Information and Communication Technologies (ICT) in English as a foreign language (EFL) classes during COVID-19. The study was done to explore the challenges experienced by the EFL teachers at a foreign languages and English preparatory school (FLEPS) at a university in North Cyprus while giving online lessons during the COVID-19 pandemic. The qualitative research approach was used in this study and the data were gathered through interviews. The participants’ sample was chosen by purposive sampling technique. Later all participants were contacted through Microsoft Teams and interviewed online for the study. Eight interviews were conducted and transcribed, which after coding process followed thematic analysis for development of themes so that the research questions of this study can be answered. The findings demonstrated the need for teachers’ Technological, Pedagogical and Content Knowledge (TPACK) trainings as well as the provision of proper infrastructure for easy access of technological tools and effective implementation of ICT into classroom. Hence, based on the findings various useful suggestions are provided which can be helpful for policy makers, educationalists, researchers and teachers for effectively incorporating ICT into their teaching and producing productive ICT lessons in online educational setup in future practice. Keywords: ICT utilization, EFL teachers, ICT adoption in classroom, COVID-19

ÖZ: Bu çalışmanın amacı, COVİD-19 sürecinde, Bilgi ve İletişim Teknolojileri’nin (BİT) yabancı dil olarak İngilizce öğretiminde etkili bir şekilde uygulanmasını olumsuz şekilde etkileyen etmenleri ortaya çıkarmaktır. Bu araştırma Kuzey Kıbrıs’ta bulunan bir üniversitenin Yabancı Diller ve İngilizce Hazırlık Okulu’nda (YDİHO) görevli İngilizce öğretmenlerinin COVID-19 pandemi sürecinde çevrimiçi derslerde yaşamış oldukları sorunları tespit etmek için yürütülmüştür. Bu çalışmada nitel araştırma yöntemi kullanılmış ve veriler görüşmeler yoluyla toplanmıştır. Araştırmanın katılımcıları amaçlı örnekleme tekniği kullanılarak seçilmiştir. Görüşmeler Microsoft Teams aracılığıyla çevrimiçi ortamda gerçekleşmiştir. Toplamda sekiz görüşme yapılmış ve görüşmeler yazıya dökülmüştür. Araştırma sorularına yanıt verebilmek için toplanan veriler tematik analiz yöntemi kullanılarak çözümlenmiştir. Araştırma bulguları öğretmenlerin Teknolojik, Pedagojik ve Alan Bilgisi (TPAB) eğitimine ihtiyaç duyduğunu ve ayrıca teknolojik araçlara kolay erişim için ve BİT’lerini etkin olarak derslerine entegre edebilmeleri için uygun altyapıya ihtiyaç duyulduğunu ortaya çıkartmıştır. Bu sebeple, bulgulara bağlı olarak yöneticilerin, eğitimcilerin, araştırmacıların ve öğretmenlerin BİT’lerini eğitime etkin bir şekilde entegre edebilmeleri ve BİT’lerini yaratıcılığı geliştirebilecek şekilde kullanmaları için çeşitli önerilere yer verilmiştir. Anahtar Kelimeler: BİT kullanımı, İngilizce öğretmenleri, sınıfta BİT'in benimsenmesi, COVID-19
Master of Education in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technology, 2021. Supervisor: Assist. Prof. Dr.İldeniz Özverir.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies in Education--Online Learning--English--Study and Teaching; Education - Computer network resources--E-Learning--English--Study and Teaching; Educational Technology--Educational Media--E-Learning--English--Study and Teaching; Teaching - Computer network resources; ICT utilization; EFL teachers; ICT adoption in classroom; COVID-19